Specialized Job Market Management to Help Graduates - Indahaslini, Indahaslini; Harapan, Edi; Wahidy, Achmad (Journal of Social Work and Science Education, 2023)
This study aims to find out and identify: (1) Implementation of the Special Job Fair (BKK) at SMK Negeri 1 Gelumbang; Obstacles faced at BKK SMK Negeri 1 Gelumbang. This study is descriptive qualitative research. The subjects were the Head of BKK, BKK staff, Principal of SMK N 1 Gelumbang, and alumni at SMK Negeri 1 Gelumbang. Data collection techniques were interviews, observations, and documentation studies. Data analysis technique was carried out in four stages: (1) data collection, (2) data reduction, (3) data presentation, (4) data withdrawal. The results of the research showed (1) Implementation of BKK SMK Negeri 1 Gelumbang Activities is carried out through Planning, Implementation, Supervision; (2) Obstacles in implementing BKK SMK Negeri 1 Gelumbang activities are internal and external obstacles.